The Use of the Game-Based Learning Model Assisted by Educandy Media to Improve Arts and Culture Learning Outcomes of Fifth-Grade Elementary School Students - Nurhidayah; Awaluddin Muin; Firdaus (PT. Lontara Digitech Indonesia, 2026)
This research is Classroom Action Research which aims to determine the use of the Game-Based Learning model assisted by Educandy media to improve the Arts and Culture learning outcomes of fifth-grade students at SD Inpres 4/82 Timurung, Ajangale District, Bone Regency. The subjects in this study were all fifth-grade students, totaling 14 students, and the fifth-grade homeroom teacher. Data collection techniques used observation and tests. The data analysis techniques in this study were data reduction, data presentation, and conclusion drawing. The results showed that the percentage of teacher activity and student activity in Cycle I reached the Fair category and in Cycle II increased to the Good category. The study showed that the Arts and Culture learning outcomes of students in Cycle I were 64.28%, or 9 students obtained an average score of 72.57 with fair qualification, and increased in Cycle II to 85.71%, or 12 students with an average score of 86.35 with good qualification. It can be concluded that the Game-Based Learning model assisted by Educandy media can improve Arts and Culture learning outcomes.